The Implementation of Group Discussion in English Speaking Class for The Seventh Grade Students - Ni’ma Amalia (Syntax Literate, 2022)
The purpose of this study is to describe the implementation of group discussion in English speaking class for the seventh-grade students of MTs Nurul Huda Medini Gajah Demak in the academic year 2017-2018 and to explain the behavior during the process of the implementation of group discussion in English speaking class for the seventh-grade students of MTs Nurul Huda Medini Gajah Demak in the academic year 2017-2018. This research used descriptive qualitative research. The techniques of collecting data used observation, interview, and documentation techniques to gather the data. The writer concluded that all students enjoyed every English learning with group discussion, they can be expert students in speaking ability and could directly share their argumentation, opinion, suggestion, and also question, because the group is not too many members. The student’s ability in A, B, and C classes to speak in front of their friends were improved. Through group discussion, they get more vocabulary to speak and more confidence to use English routinely, although they still made grammatical mistakes and their punctuation was not perfect. Surely, in group discussion, the students were more cooperative with their group to share their ideas, even sometimes the situation was crowded because all of the students are active to discuss with their group. During this simple method applied, the students are more enthusiastic because they were not working individually.